Biomorph growth in single-phase systems: expanding the structure spectrum and pH range. Issue 10 (22nd December 2015) - Nakouzi, Elias; Knoll, Pamela; Steinbock, Oliver
Abstract : Biomorphs are life-like microstructures of selfassembled barium carbonate nanorods and silica. Abstract : Biomorphs are life-like microstructures of selfassembled barium carbonate nanorods and silica. In a departure from established approaches, we produce biomorphs in CO2 - and gradient-free solutions. Our study reveals novel structural motifs for solution-grown biomorphs, reduces pH transients, and expands the upper pH limit for biomorph formation to over 12 where silica is essentially soluble.